The Transformative Role of Information and Communication Technologies in Shaping Gender Norms and Empowering Women: Evidence From Pakistan and Nepal - Md. Jahirul Islam (Violence against women, 2024)
This study explores how information and communication technologies (ICTs) influence transforming attitudes toward intimate partner violence (IPV) and women's empowerment in Pakistan and Nepal. By analyzing data from married women using recent Demographic and Health Surveys, the research reveals that owning multiple ICTs is associated with decreased experiences of physical IPV and reduced acceptance of wife-beating. Notably, increased ownership of ICTs corresponds to heightened participation in household decisions. Furthermore, regular internet use further diminishes the likelihood of experiencing physical IPV and justifying wife-beating. These findings underscore ICTs’ potential to empower women, reshape gender norms, and enhance decision-making autonomy. The study advocates for gender-inclusive policy interventions that leverage the transformative influence of ICTs in fostering positive sociocultural changes.